Efficiency Measurement of Nottingham Primary Schools with DEA Model - Chen, Han (2006)
This paper aims to assess the factors that can influence efficiency performance of primary schools in Nottinghamshire LEA. Data from OFSTED database is used for evaluation by means of Data Envelopment Analysis (DEA). 65 primary schools are finally selected for assessment because of data availability, and 3 input/output indicators are implemented in the final VRS output orientated DEA model. It is found that social-economic background, such as the school areas, poverty level indicated by rate of pupils eligible for free lunch, plays an important role in schools efficiency performance, especially academic results obtain the most influence. It can also be stated that the schools efficiency performance improved slightly during the last five year, while the productivity changed slightly in a negative way.